(untitled) (International Journal of Irrigation and Water Management, 2019)
A series of experiment on water samples at different depths of aquifer was conducted to find out the suitability for irrigation and drinking water quality in relation to arsenic contamination. All the groundwater samples in deep aquifer for irrigation were almost good in respect of electrical conductivity (EC), normal in respect of sodium adsorption ratio (SAR), satisfactory in respect to residual sodium bi-carbonate (RSBC), good in respect of permeability index (PI), soft to very hard with respect to total hardness (TH), good to doubtful for soluble sodium percentage (SSP) and practically neutral to slightly alkaline in respect of pH. Excepting a few, the water samples were not harmful to soil in respect of magnesium adsorption ratio (MAR) and Kelly’s ratio (KR). Iron concentrations were far below the recommended upper limit of irrigation water except magnesium. All water quality parameters were found to be correlated with each other. Most of the groundwater samples at shallow aquifer were not suitable for drinking purpose in relation to arsenic (< 0.05 mgL-1 ) in that area